Spectres of Post-marxism? Reassessing Key Post-Marxist Texts. Issue 2 (1st April 2019) - Sim, Stuart
Abstract : The emergence of a movement of post-Marxist thought from the 1970s onwards brought to attention a series of texts all offering a highly critical reading of the Marxist tradition, broadly speaking from the perspective of poststructuralist and postmodernist theory. JeanFrançois Lyotard's Libidinal economy, Jean Baudrillard's The mirror of production, Ernesto Laclau and Chantal Mouffe's Hegemony and socialist strategy, and Jacques Derrida's Spectres of Marx constituted a sustained critique of Marxism and its cultural legacy, ranging in approach from outright rejection to calls for substantial revision of its main concepts. The effect was to generate considerable controversy across the left. But what has been the legacy of each text: a dead end, or a signpost to the future of left-wing thought? This article reassesses these four key works to consider the extent to which they still resonate meaningfully today, either theoretically or politically, given the many social changes that have occurred in the interim.